2010
DOI: 10.1073/pnas.1003653107
|View full text |Cite
|
Sign up to set email alerts
|

Protein complexing in a methanogen suggests electron bifurcation and electron delivery from formate to heterodisulfide reductase

Abstract: In methanogenic Archaea, the final step of methanogenesis generates methane and a heterodisulfide of coenzyme M and coenzyme B (CoM-S-S-CoB). Reduction of this heterodisulfide by heterodisulfide reductase to regenerate HS-CoM and HS-CoB is an exergonic process. Thauer et al. [Thauer, et al. 2008 Nat Rev Microbiol 6:579-591] recently suggested that in hydrogenotrophic methanogens the energy of heterodisulfide reduction powers the most endergonic reaction in the pathway, catalyzed by the formylmethanofuran dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 35 publications
1
183
1
Order By: Relevance
“…The proximity of MvhD to HdrABC ( Figure 5) suggests that this subunit could interface with HdrABC during electron bifurcation as previously demonstrated in the Methanococcales order (Costa et al, 2013). However, the organization of Mvh subunits ( Figure 6) and lack of homologs to MvhB differs to what has been observed in M. maripaludis (Costa et al, 2010) where experimental evidence showed that proximally encoded MvhABGD subunits (canonical enzyme system) mediated electron bifurcation. Overall, this indicates that there are profound differences in the mechanisms of electron bifurcation (particularly in the generation of low potential electrons) within the Methanomicrobiales and between the Methanomicrobiales and other orders of cytochrome-deficient methanogens.…”
Section: Analysis Of Primary Metabolic Genes Reveals Different Lifestcontrasting
confidence: 44%
See 1 more Smart Citation
“…The proximity of MvhD to HdrABC ( Figure 5) suggests that this subunit could interface with HdrABC during electron bifurcation as previously demonstrated in the Methanococcales order (Costa et al, 2013). However, the organization of Mvh subunits ( Figure 6) and lack of homologs to MvhB differs to what has been observed in M. maripaludis (Costa et al, 2010) where experimental evidence showed that proximally encoded MvhABGD subunits (canonical enzyme system) mediated electron bifurcation. Overall, this indicates that there are profound differences in the mechanisms of electron bifurcation (particularly in the generation of low potential electrons) within the Methanomicrobiales and between the Methanomicrobiales and other orders of cytochrome-deficient methanogens.…”
Section: Analysis Of Primary Metabolic Genes Reveals Different Lifestcontrasting
confidence: 44%
“…All strains had a cytoplasmic F 420 -reducing hydrogenase, but they showed differential gene content at other steps of methanogenesis. In distantly related orders of cytochrome-deficient methanogens, the Methanobacteriales and Methanococcales, it was shown, during hydrogenotrophic methanogenesis, that two pairs of electrons are bifurcated in a process whereby the exergonic reduction of the coenzyme M-coenzyme B heterodisulfide is energetically coupled to the endergonic production of formyl-methanofuran, in a protein complex that incorporates cytoplasmic heterodisulfide reductase (HdrABC), formyl-methanofuran dehydrogenase, subunit D of Mvh and one of either formate dehydrogenase (Fdh), MvhABG, or an F 420 -reducing hydrogenase (Costa et al, 2010) (Figure 4). The proximity of MvhD to HdrABC ( Figure 5) suggests that this subunit could interface with HdrABC during electron bifurcation as previously demonstrated in the Methanococcales order (Costa et al, 2013).…”
Section: Analysis Of Primary Metabolic Genes Reveals Different Lifestmentioning
confidence: 99%
“…Fig. 5 does not take the recent evidence into account that in Methanococcus maripaludis the MvhADG/HdrABC complex forms a supercomplex with the formylmethanofuran dehydrogenase complex (38) and that therefore the first and the last step of methanogenesis from H 2 and CO 2 proceed in close proximity which was already proposed 20 y ago in a review by Rouvier and Wolfe (39).…”
Section: Discussionmentioning
confidence: 99%
“…The Hdr-associated hydrogenases (Vhu and Vhc) (Fig. 1), which provide electrons to the last reductive step of methanogenesis and potentially the first step via electron bifurcation (1,6,7), can be substituted by formate dehydrogenase (Fdh) during growth on formate (7). The F 420 -reducing hydrogenases (Fru and Frc) generate F 420 H 2 for the second and third reductive steps of methanogenesis, but the Fdh is also F 420 reducing (12,13).…”
Section: Resultsmentioning
confidence: 99%